2022
DOI: 10.3126/nmcj.v24i2.46029
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge regarding obstetric danger signs among pregnant women

Abstract: Knowledge of obstetric danger signs is crucial to reduce maternal morbidity and mortality by identifying the problems earlier and avoiding the delay in seeking obstetric care. According to World Health Organization (WHO) more than 70% of maternal deaths occur due to obstetric complications and most of these deaths occur in developing countries. Most of these are preventable if pregnant women can identify these life-threatening danger signs on time and seek appropriate emergency obstetric care. This study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
5
2
Order By: Relevance
“…In the present study, more than half 77 (55.4%) of women were multi gravida mother which is similar to a study conducted in Nepal by Ghimire B, Pathak P, Ghimire P study revealed that 52.1% were multi gravida, also similar to study conducted in Wolaita Sodo town, South Ethiopia by Bolanko A, et.al, study revealed that most (57.7%) were multi gravida. [5,13] Nearly half 66 (47.5%) of the women had one child which is contrast to a study conducted in Nepal by Ghimire B, Pathak P, Ghimire P study showed that most of the respondents (86.5%) had one child. 5…”
Section: Obstetric Characteristics Of the Postnatal Mothercontrasting
confidence: 59%
See 2 more Smart Citations
“…In the present study, more than half 77 (55.4%) of women were multi gravida mother which is similar to a study conducted in Nepal by Ghimire B, Pathak P, Ghimire P study revealed that 52.1% were multi gravida, also similar to study conducted in Wolaita Sodo town, South Ethiopia by Bolanko A, et.al, study revealed that most (57.7%) were multi gravida. [5,13] Nearly half 66 (47.5%) of the women had one child which is contrast to a study conducted in Nepal by Ghimire B, Pathak P, Ghimire P study showed that most of the respondents (86.5%) had one child. 5…”
Section: Obstetric Characteristics Of the Postnatal Mothercontrasting
confidence: 59%
“…[5,13] Nearly half 66 (47.5%) of the women had one child which is contrast to a study conducted in Nepal by Ghimire B, Pathak P, Ghimire P study showed that most of the respondents (86.5%) had one child. 5…”
Section: Obstetric Characteristics Of the Postnatal Mothercontrasting
confidence: 59%
See 1 more Smart Citation
“…31 The finding that the prevalence of good ODS knowledge in Thai pregnant women was slightly higher than that of the Malaysian study might be due to the different score cut-off levels of good knowledge of ODS, that is, 80% (16 out of 20 items) in the Malaysian study whereas 75% (12 out of 16 items) in our study and the other Thai study. Several studies reported the knowledge of ODS among pregnant women in many countries, including India, 34,35 Nepal, 26,27 Malaysia, 31 Ethiopia, [10][11][12][13][14][15][16][17][18][19][20][21][22] Nigeria, 23 Tanzania, 28 Egypt, 29 Jordan, 30 Congo, 36 and Uganda. 37 The prevalence of mothers with good knowledge of ODS differed among studies could be because of the difference in participants' demographic characteristics and the definition of good knowledge of ODS in each study.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies found that less than half of the study population had good knowledge of ODS. [10][11][12]14,17,18,21,27,[29][30][31][32] In addition, the prevalence of good knowledge or awareness of ODS in rural areas was lower than in urban areas. One study was conducted to examine the prevalence of mothers with good knowledge of ODS and associated factors in a tertiary care university hospital in the capital city of Thailand and found that the prevalence of mothers with good knowledge was around 60%.…”
Section: Introductionmentioning
confidence: 99%